Comparison of measurement uncertainty between ISO/GUM and method validation approach of mercury - Chaengthong, Neeranart (Bulletin of Applied Sciences, 2014)
Measurement results from chemical testing laboratories that can be interntionally acceptable need to apply Metrology in Chemistry (MIC) which is an important science of measurement. The key principles of MiC includes metrological traceability, method validation and uncertainty of measurement which are the factors that laboratories need to demonstrate to comply with ISO/IEC 17025. This studies concerned with comparison of the estimation of measurement uncertainty of determination of mercury in drinking water by using ISO/GUM approach and method validation approach. There were many sources of uncertainties when using ISO/GUM approach such as precision, volumes of samples, volumes of blank and concentration of samples. Meanwhile method validation approach had only precision and bias. It was found that the expanded uncertainties were 8.5% and 11%, respectively. The estimation of measurement uncertainty in this paper can be applied to other measurement methods that using calibration curves.